Intimate partner violence and antiretroviral therapy initiation among female sex workers newly diagnosed with HIV in Zambia: a prospective study - Oldenburg, Catherine; Ortblad, Katrina F.; Chanda, Michael M.; Mwale, Magdalene; Chongo, Steven; Kanchele, Catherine; Kamungoma, Nyambe; Fullem, Andrew; Bärnighausen, Till (Journal of acquired immune deficiency syndromes, 2018)
Background: Intimate partner violence (IPV) is common among female sex workers (FSW) globally. Here, we prospectively assessed the relationship between IPV and engagement in HIV care in a cohort of FSW who had been newly diagnosed with HIV. - Methods: Data arose from the Zambian Peer Educators for HIV Self-Testing study, a randomized controlled trial of HIV self-test distribution among FSW in 3 transit towns in Zambia. Participants were self-reported to be HIV-uninfected or unaware of their status at baseline. IPV in the previous 12 months was assessed at baseline. At 4 months, participants were asked the results of their last HIV test and those who reported testing positive were asked whether they had engaged in HIV-related care and started antiretroviral therapy (ART). - Results: Of 964 participants, 234 (24.3%) reported that they were living with HIV at 4 months. Of these 234 participants, 142 (60.7%) reported a history of IPV (past 12 months) at baseline and at 4 months, 152 (65.0%) reported that they were in HIV-related care, and 132 (56.7%) reported that they had initiated ART. Participants who reported IPV had significantly reduced odds of engagement in care (adjusted odds ratio = 0.48, 95% confidence interval: 0.26 to 0.91) and ART initiation (adjusted odds ratio = 0.40, 95% confidence interval: 0.22 to 0.72). - Conclusions: FSW living with HIV in Zambia reported very high rates of IPV. Structural and individual interventions for violence prevention are urgently needed to better protect this population. Given the strong negative relationship between IPV and engagement in HIV-related care, such interventions could also substantially improve HIV-related health outcomes.